FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKSUAL REMAJA AWAL DI LINGKUNGAN PROSTITUSI BANDUNGAN KABUPATEN SEMARANG - Isnaini Maulidya; Syamsulhuda Budi Musthofa; Ratih Indraswari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Adolescents who lived in prostitution complex have unhealthy condition of environment that can affect their development, morality, and form improperly behavior. This study aimed to determine factors correlated with early adolescent sexual behavior in prostitution complex of Bandungan. This was an analytic-descriptive study with cross sectional study design. This study included 60 samples of early adolescents in Bandungan (10-14 years old) who were selected using proportional random sampling technique. Data were obtained from interview and online survey. Chi square analysis showed parents’ job (p=0,037), environment (p=0,025), and quality of sexuality communication with parents (p=0,002) had significant correlation with adolescent sexual behavior. Knowledge about sexuality (p=0,750) and frequency of sexuality communication with parents (p=0,768) were not significantly correlated with adolescent sexual behavior.Therefore, findings suggest local government and community to create a healthy environment by holding positive activities and enacting regulations that support children protection as well as parents should improve the quality of sexuality communication with their children.